2009
DOI: 10.1097/ccm.0b013e31819df06b
|View full text |Cite
|
Sign up to set email alerts
|

Stratification is the key: Inflammatory biomarkers accurately direct immunomodulatory therapy in experimental sepsis*

Abstract: Objective This study examined the effectiveness of prospective stratification to identify and target high-dose glucocorticoid therapy for subjects developing lethal sepsis. Design Prospective, randomized, laboratory-controlled experiment. Setting University research laboratory. Subjects Adult female outbred CD-1 mice. Interventions Mice (n = 88) were subjected to sepsis induced by cecal ligation and puncture (CLP). Mice were prospectively divided into two groups, predicted to die (P-DIE) or predicted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
102
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 44 publications
2
102
1
2
Order By: Relevance
“…In a murine cecal ligation and puncture model of septic shock, levels of IL-6 at 6 hours following onset of sepsis were predictive of outcome [34]. Whilst the effect of Il-6 on cardiac myoctes has largely been assumed to be due to transignaling from binding of IL-6 to soluble receptor in serum and subsequent activation via cell surface gp130 receptor, our data in both rat and human cardiac myocytes show a direct negative inotropic effect of IL-6 in the absence of the soluble receptor [12], suggesting that classical signaling via a cell surface IL-6 receptor also occurs.…”
Section: Discussionmentioning
confidence: 99%
“…In a murine cecal ligation and puncture model of septic shock, levels of IL-6 at 6 hours following onset of sepsis were predictive of outcome [34]. Whilst the effect of Il-6 on cardiac myoctes has largely been assumed to be due to transignaling from binding of IL-6 to soluble receptor in serum and subsequent activation via cell surface gp130 receptor, our data in both rat and human cardiac myocytes show a direct negative inotropic effect of IL-6 in the absence of the soluble receptor [12], suggesting that classical signaling via a cell surface IL-6 receptor also occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Although our results were adjusted for multiple comparisons, relevant covariates, and population stratification, and although we used functional assays to demonstrate in vitro effects of SNPs, we underscore the limitations of our sample size and the need for replication in independent studies. The early tailoring of treatments has been beneficial for outcomes of sepsis in animal models (47). Therefore, an early classification of patients, based on their genetics to predict immunomodulatory status, may offer benefits in more specific therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies, as well as recent human studies, have highlighted the importance of delayed sepsis-induced immunosuppression and its contribution to the mortality of the syndrome (14). Several researchers have shown that the levels of both proinflammatory and anti-inflammatory cytokines can be correlated with the severity of illness (26,27,29). For example, IL-10, a potent anti-inflammatory cytokine, has been shown to predict poor prognosis in patients with sepsis, and modulation of IL-10 in selected animal models of sepsis improved survival (15,16,34; M. Ariefdjohan, K. Queensland, L. Weitzel, D. Heyland, and P. Wischmeyer, presented at the 32nd Annual Conference on Shock, San Antonio, TX, 2009).…”
mentioning
confidence: 99%